ANALISIS VALUE FOR MONEY PADA KINERJA ANGGARAN REALISASI DINAS SOSIAL KABUPATEN BENGKALIS PROVINSI RIAU - Ikhsan Abdul Rahman; Efi Susanti (Journal Of Islamic Finance And Accounting Research, 2023)
This study aims to analyze the performance accountability of the Bengkalis District Social Servicethrough the principle of value for money. The type of research used is qualitative. Data collectiontechniques used are documentation and interviews. The data obtained are in the form of Performance Reports of Government Agencies of the Bengkalis Regency Social Service in 2020 and 2021. The results of this study indicate that in 2020 the economic calculation with a ratio value of 97.12% is categorized as economic, the efficiency calculation with a ratio value of 102.79% is said to be efficient. , and the calculation of effectiveness with a ratio value of 106.76%is categorized as effectiveness. In 2021 economic calculations with a ratio value of 88.91% are categorized as economical, efficiency calculations with a ratio value of 110.67% are categorizedas efficient, and effectiveness calculations with a ratio value of 99.14% are categorized as ineffective. Thus, the performance of the Bengkalis District Social Service in 2020 and 2021 in terms of economic, efficiency, and effectiveness (3E) elements has not met the value for money principle.